THE USE OF PICTURE SERIES TO IMPROVE STUDENTS' READING COMPREHENSION: A CASE STUDY AT 9TH GRADE OF SMP N 1 ROWOSARI-KENDAL - Siti Mundhiyanti; Siti Nur’aini; Dyah Nugrahani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT The purpose of this research is to find out whether the use of picture series can improve reading comprehension of descriptive text material for grade 9 students of SMP N 1 Rowosari. This research aims to (1)To find out the implications of using picture series media in improving reading comprehension of students' descriptive texts in class. (2)To explain the benefits that students get in class related to the use of picture series media to improve reading comprehension in descriptive texts. In this study, researchers used a qualitative descriptive research method. The subjects involved in this research were 30 grade 9E students of SMP N 1 Rowosari. The research instruments used to collect data for data analysis were in the form of pre-tests, post-tests, and questionnaires. The results of the study revealed that the use of picture series to improve reading comprehension can help improve students' ability to understand reading in descriptive texts. The results obtained show that the average pre-test score is 63.67 and the post-test average is 81.33. It can be concluded that there is an increase in students' reading comprehension. This also implies that picture series can improve students' reading comprehension and contribute to increasing students' reading scores and comprehension. In addition, data from the questionnaire results show that students gave positive answers to the questions given in the questionnaire. Keywords: Reading Comprehension, Picture Series, Descriptive Text.